PENGUATAN KELEMBAGAAN MELALUI SEKOLAH HIJAU BERKELANJUTAN - Kuswati, Rini; Waskito, Jati; Achmad, Nur; Soepatini, S; Irawati, Zulfa; Abas, Novel Idris; Choirunnisa, Bella A.; Ahmadi, Mirzam Arqy; Angellia, Anggi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
This community dedication program is intended to assist partners in the preparation of institutions to become sustainable green schools. This is a community-based activity that promotes the circular economy, particularly in elementary schools staffed by parents, students, and faculty, as well as the adjacent area. Activities for promotion, instruction on the significance of adiwiyata schools, and a sequence of initiatives aimed at enhancing the efficacy of communication, in addition to the construction of facilities at the adjutant school.